Household Registration System, Migration, and Inequity in Healthcare Access - Yuan, Bocong (Healthcare (Basel), 2019)
This study investigates the influence of the household registration system on rural–urban disparity in healthcare access (including healthcare quality, blood pressure check, blood test, vision test, dental examination, and breast exam), using data from a large-scale nationwide life history survey that covered 150 counties across 28 provinces and municipalities in China. In contrast to the findings of many previous studies that emphasize the disparity in the residence place as the cause of rural–urban disparity in healthcare access, this study finds that the residence place just has a very limited influence on healthcare access in China, and what really matters is the household registration type. Our empirical results show that people with a non-rural household registration type generally have better healthcare access than those with a rural one. For rural residents, changing the registration type of their household (from rural to non-rural) can improve their healthcare access, whereas changing the residence place or migrating from rural to urban areas have no effect. Therefore, mere rural-to-urban migration may not be a valid measure to eliminate the rural–urban disparity in healthcare access, unless the institution of healthcare resource allocation is reformed.